2001
DOI: 10.1037/0022-3514.81.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Emotional selection in memes: The case of urban legends.

Abstract: This article explores how much memes like urban legends succeed on the basis of informational selection (i.e., truth or a moral lesson) and emotional selection (i.e., the ability to evoke emotions like anger, fear, or disgust). The article focuses on disgust because its elicitors have been precisely described. In Study 1, with controls for informational factors like truth, people were more willing to pass along stories that elicited stronger disgust. Study 2 randomly sampled legends and created versions that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
396
5
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(442 citation statements)
references
References 34 publications
20
396
5
7
Order By: Relevance
“…A result replicated by several independent labs is that information about social relationships is transmitted with higher fidelity than equivalent non-social information (McGuigan and Cubillo 2013; Mesoudi et al 2006;Reysen et al 2011;Stubbersfield et al 2014), as predicted by social brain theories of the biological evolution of primate cognition (Dunbar 2003). There is also experimental support for a bias for emotionally salient disgust-inducing information (Eriksson and Coultas 2014;Heath et al 2001). Xu et al (2013), meanwhile, found that initially random colour terms transmitted along chains of people gradually converged on those colour terms commonly seen across actual societies, arguing that the innate features of our perceptual system makes certain colours more salient and thus more likely to emerge through repeated transmission.…”
Section: Cognitive Biases Can Drive Cultural Evolution Towards Culturmentioning
confidence: 50%
See 1 more Smart Citation
“…A result replicated by several independent labs is that information about social relationships is transmitted with higher fidelity than equivalent non-social information (McGuigan and Cubillo 2013; Mesoudi et al 2006;Reysen et al 2011;Stubbersfield et al 2014), as predicted by social brain theories of the biological evolution of primate cognition (Dunbar 2003). There is also experimental support for a bias for emotionally salient disgust-inducing information (Eriksson and Coultas 2014;Heath et al 2001). Xu et al (2013), meanwhile, found that initially random colour terms transmitted along chains of people gradually converged on those colour terms commonly seen across actual societies, arguing that the innate features of our perceptual system makes certain colours more salient and thus more likely to emerge through repeated transmission.…”
Section: Cognitive Biases Can Drive Cultural Evolution Towards Culturmentioning
confidence: 50%
“…Interestingly, similar inductive biases to those observed by Kirby et al (2008) have been shown in songbirds, where repeated learning constraints generate structure in songs in the same way that repeated learning constraints generate structure in languages (Feher et al 2009). prevalence of disgusting information in real-life urban legends (Heath et al 2001), while near-universal aspects of grammar and colour terminology can be explained in terms of repeated transmission constraints (Kirby et al 2008;Xu et al 2013). A key finding of many of these studies is that weak individual biases can be easily magnified at the population level, in a way that could not be anticipated by focusing on individual cognition alone.…”
Section: Cognitive Biases Can Drive Cultural Evolution Towards Culturmentioning
confidence: 91%
“…These content biases are, in turn, often explained by appeal to the operation and properties of psychological mechanisms. For example, Heath et al (2001) showed how the psychology of disgust can influence the horizontal transmission of cultural variants. They found that the more likely an urban legend was to trigger disgust, the more likely it was to be passed along to peers and to appear on urban legend Web sites.…”
Section: Agustín Fuentesmentioning
confidence: 99%
“…Experiment 1 was a classical serial reproduction experiment, conducted to test whether stories are better retained along a transmission chain if they contain a disgusting element. In other words, we investigated emotional selection in the encode-and-retrieve phase of cultural transmission.In addition, we asked participants to rate each story component on the likelihood that they would pass along such a story, in order to replicate the finding of Heath et al (2001).A concern with the argument that the effect of disgust manipulations can be attributed to elicitation of negative emotions was that disgusting elements are also known to be capable of evoking amusement (Rozin, Haidt and McCauley, 2008b;McGraw and Warren, 2010). In Experiment 2 we therefore used a survey to collect ratings of the same stories on how humorous they were, and also on all qualities previously found to be important predictors of pass along ratings (Heath et al, 2001).…”
mentioning
confidence: 99%